БАЛАНЫҢ ФИЗИОЛОГИЯЛЫҚ РАЎАЖЛАНЫЎЫНА ФИЗИКАЛЫҚ ШЫНЫҒЫЎЛАР ҲӘМ ҲӘРЕКЕТЛИ ОЙЫНЛАРДЫҢ ТӘСИРИ - Мырзамбетов, П.; Аспетуллаев, А. (FAN va JAMIYAT, 2016)
The article deals with the problems of physiological development of children of school age and the influence of physiological training and out door games. The article gives a proper attention to the Karakalpak national outdoor game «Qasharman top» as a game insuring physiological development of children.